Dark Energy with Phantom Crossing and the H0 Tension - Eleonora Di Valentino; Ankan Mukherjee; Anjan A. Sen (Entropy, 2021)
We investigate the possibility of phantom crossing in the dark energy sector and the solution for the Hubble tension between early and late universe observations. We use robust combinations of different cosmological observations, namely the Cosmic Microwave Background (CMB), local measurement of Hubble constant (<semantics>H0</semantics>), Baryon Acoustic Oscillation (BAO) and SnIa for this purpose. For a combination of CMB+BAO data that is related to early universe physics, phantom crossing in the dark energy sector was confirmed at a 95% confidence level and we obtained the constraint <semantics>H0=<msubsup>71.0−3.8+2.9</msubsup></semantics> km/s/Mpc at a 68% confidence level, which is in perfect agreement with the local measurement by Riess et al. We show that constraints from different combinations of data are consistent with each other and all of them are consistent with phantom crossing in the dark energy sector. For the combination of all data considered, we obtained the constraint <semantics>H0=70.25±0.78</semantics> km/s/Mpc at a 68% confidence level and the phantom crossing happening at the scale factor <semantics>am=<msubsup>0.851−0.031+0.048</msubsup></semantics> at a 68% confidence level.